Analysis of Supporting and Inhibiting Factors in Learning at Community Learning Activity Centers - Emilda Kholifah Arifah; Triana Rosalina Noor (Pondok pesantren As-salafiyah As-Safi'iyyah, 2025)
This research is classified as qualitative case study research which aims to identify supporting and inhibiting factors for the formation of learning at the Community Learning Activity Center (PKBM) Sekolah Alam Rumah Matahari Sidoarjo. Data collection methods used were observation, interviews and documentation. Interviews were conducted with the principal, teachers, committee and students at Alam Rumah Matahari School. The data analysis techniques used are through the stages of data reduction, data presentation, and drawing conclusions. The results of this research show that there are factors that influence and inhibit nature-based learning at PKBM Rumah Matahari Nature School Sidoarjo. The supporting factors found were competent teachers, high enthusiasm from students, and adequate infrastructure. On the other hand, the inhibiting factors encountered include limited teaching staff, unfavorable weather conditions, and public perception of the PKBM learning method which is still underestimated.